Menganalisis Influencer Marketing di Media Sosial: Bagaimana Endorsement dan Brand Image Mempengaruhi Keputusan Pembelian Konsumen yang di Mediasi oleh Kepercayaan Konsumen - Zahra Ayu Azizah; Sri Padmantyo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of endorsement and brand image on purchasing decisions, where consumer trust is a moderating variable for Tiktok social media users. Writing this thesis uses a descriptive writing method with a quantitative approach and collects data using a questionnaire. The data used is primary data obtained from the results of a questionnaire with a sample size of 200 respondents using the Tiktok social media. The population of this research is Tiktok social media users in the city of Surakarta, Central Java. This research uses Smart PLS 3.0 as a data analysis tool. The tests used are validity tests, reliability tests, classic multicollinearity assumption tests, R2 tests, Q2 tests, path coefficient tests, hypothesis tests. The research results found that brand image has a positive and significant effect on consumer purchasing decisions. Endorsements have a positive and significant effect on consumer purchasing decisions. Consumer trust can moderate endorsement of consumer purchasing decisions. Meanwhile, consumer trust cannot moderate brand image on consumer purchasing decisions.